Composite material for frame structure and preparation process thereof
By combining the composite process of using γ-aminopropyltriethoxysilane and dextran in automotive materials and the black phosphorus-graphene composite material, the problems of poor mechanical properties and high cost of existing automotive materials are solved, and high-performance composite materials suitable for automotive frame structures are prepared.
Patent Information
- Application Number
- CN202411794072.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The existing automotive materials have poor mechanical properties and high cost of plastic composite materials, resulting in limited application in the automotive field.
Using a preparation process for a composite material for frame structure, composite materials with excellent mechanical properties are prepared by treating γ-aminopropyltriethoxysilane and dextran and compounding materials after treatment with black phosphorus-graphene composite materials, and adding inorganic fillers and coupling agents.
It has achieved the reduction of material costs and improved mechanical properties, especially in terms of impact strength, bending strength and elongation of break, and is suitable for the frame structure in the automotive field.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of engineering plastics, and in particular to a composite material for a frame structure and a preparation process thereof. Background Art
[0002] There are two main types of materials that can be used to reduce vehicle weight. One type is high-strength materials, such as high-strength steel, which has always been the most used material in automobile production. At the same strength level, the thickness of the steel plate can be reduced to reduce the weight of the vehicle body, but as the strength of the steel plate increases, many problems such as decreased forming performance will occur. The other type is lightweight materials, including aluminum alloys, magnesium alloys, plastics, composite materials, etc. The density of aluminum alloys is about 1 / 3 of that of steel. It is widely used and has advantages such as high thermal conductivity and good corrosion resistance, but welding processability and cost control are application bottlenecks; magnesium alloys have high specific strength and specific stiffness, and the lightweight effect is more significant. They also have advantages such as damping and vibration reduction. However, due to technical conditions, the manufacturing process cost is high and there are deficiencies in strength and other aspects; plastics have a small specific gravity and good corrosion resistance, and are important lightweight materials. There is a trend of increasing the proportion of applications in new energy vehicles, but there are problems such as insufficient strength. Composite materials came into being to address the deficiencies of plastics and have characteristics such as high strength.
[0003] To sum up, various types of weight-reducing materials have their own characteristics and application status. High-strength steel plays an important role in automobile production but its application is challenging. Lightweight materials have their own advantages and limitations. They have different development trends and research directions in the process of automobile lightweighting. In the future, we need to continuously improve technology and overcome shortcomings to better promote the development of the automotive industry.
[0004] Invention patent CN107903627A discloses a thermoplastic lightweight composite material, whose components include 20-30 parts of modified carbon fiber, 80-84 parts of polyimide powder, 10-15 parts of modified glass fiber, 10-12 parts of heat stabilizer and 15-20 parts of antioxidant. The specific formula enables the composite material to have greatly improved interface compatibility, adhesion, strength and firmness under the synergistic effect of various substances.
[0005] Invention patent CN108727790A proposes a lightweight environmentally friendly engineering plastic for automobiles. The raw materials include 55.9-70.0 parts of base resin (one or more of PA66, PA6, PA610), 7.5-9.5 parts of toughening agent, 70.5-85.5 parts of polyethylene terephthalate, 1.0-3.5 parts of compatibilizer (POE-g-MAH), 0-1.5 parts of antioxidant, 0.7-1.5 parts of nano zirconium dioxide, 0.7-2.8 parts of coupling agent (3-aminotriethoxysilane), 12.5-15.0 parts of carbon fiber, and 1.0-1.5 parts of alkali-free glass fiber. The environmentally friendly engineering plastic has excellent mechanical properties, can reduce automobile weight, and reduce energy consumption and exhaust emissions.
[0006] At present, most of the preparation of plastic composite materials uses carbon fiber or modified carbon fiber and plastic composite, but the high price of carbon fiber leads to high cost of the prepared composite material, which is not conducive to the widespread use of plastic composite materials in the automotive field. Therefore, it will be of great application value to prepare a composite material for frame structure with lighter weight, excellent mechanical properties and relatively low cost. Summary of the invention
[0007] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is that the mechanical properties of the existing automotive materials are poor and the prepared plastic composite materials are expensive. The purpose of the present invention is to provide a preparation process of a composite material for a frame structure with low cost and excellent mechanical properties, comprising the following steps:
[0008] S1: Weigh 1-5 parts by weight of γ-aminopropyltriethoxysilane and add it to 100-200 parts by weight of 70-80 wt% ethanol aqueous solution and stir for 1-2 hours;
[0009] S2 weighs 30 to 60 parts by weight of dextran and adds it to the mixed solution in step S1, and stirs for 2 to 4 hours to treat the dextran;
[0010] After the stirring in S3 is completed, the mixed solution is concentrated to dryness at 40-50°C and 0.09MPa0.07-0.09MPa, and then dried at 60-70°C for 10-12h to obtain the treated glucan;
[0011] S4: weigh 1-2 parts by weight of black phosphorus and disperse it in 100-200 parts by weight of water, ultrasonicate it at 0-5°C, 400-450W, 40-45kHz for 5-6h, centrifuge it at 4000-4500rpm for 1-2h, and take the supernatant;
[0012] S5: weighing 10-20 parts by weight of graphene oxide and dispersing it in 1000-1500 parts by weight of water, adding the supernatant in step S4, ultrasonicating at 10-20° C., 400-450 W, 40-45 kHz for 1-2 hours, stirring for 20-24 hours, adding 10-20 parts by weight of HI aqueous solution for reduction, stirring for 5-6 hours, filtering, and drying the filter cake at 50-60° C. for 10-12 hours to obtain a black phosphorus-graphene composite material;
[0013] S6: 100-200 parts by weight of caprolactam, 30-40 parts by weight of dextran treated in step S3, 5-10 parts by weight of black phosphorus-graphene composite material, 10-20 parts by weight of inorganic filler, and 1-2 parts by weight of coupling agent are mixed, and the mixed materials are melt-extruded, granulated, and dried to obtain a composite material for a frame structure. The process control conditions are: 170-175°C in zone 1, 170-175°C in zone 2, 175-180°C in zone 3, 175-180°C in zone 4, 180-185°C in zone 5, 180-185°C in zone 6, 185-190°C in zone 7, and 185-190°C in zone 8; the residence time is 2-4 minutes, and the pressure is 12-18 MPa.
[0014] Furthermore, the inorganic filler in step S6 is one of calcium carbonate, talcum powder or glass fiber;
[0015] Furthermore, the coupling agent in step S6 is one of styrene or methyl methacrylate;
[0016] Furthermore, in step S6, the drying temperature is 60-80° C. and the drying time is 10-12 hours.
[0017] The present invention also provides a composite material for a frame structure prepared by the above-mentioned preparation method. Compared with the prior art, the present invention solves the problem that most plastic composite materials in the prior art have high costs and poor mechanical properties and are not conducive to market promotion. The beneficial effects of the present invention are as follows:
[0018] (1) The present invention provides a composite material for a frame structure and a preparation process thereof, wherein the problem of low strength of the plastic material is improved by compounding nylon 6 with treated dextran and black phosphorus-graphene composite materials, and the addition of graphene brings certain flame retardancy to the composite material;
[0019] (2) The prepared framework structure composite material adds treated dextran to replace part of the lightweight filler, which reduces the density of the material and maintains a good bending modulus. The hydroxyl groups of the polysaccharide molecules are combined with γ-aminopropyltriethoxysilane, which increases the dispersibility of dextran in the polymer and improves its compatibility with the material.
[0020] (3) The lubricating effect of black phosphorus greatly enhances the toughness of graphene, and the covalent cross-linking produced by the two improves the mechanical properties of the composite material, making this material have good application prospects in the automotive field. DETAILED DESCRIPTION
[0021] The technical scheme in the embodiments of the present invention is described clearly and completely below. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. The operations involved in the embodiments are all conventional technical operations in the art unless otherwise specified. Introduction of some raw materials in this application:
[0022] Some raw material parameters in the embodiments of the present invention are as follows:
[0023] Dextran, CAS number: 9004-5-0, was purchased from Beijing Bailingwei Technology Co., Ltd.
[0024] γ-Aminopropyltriethoxysilane, CAS No.: 919-30-2, was purchased from Aladdin.
[0025] Black phosphorus, CAS number: 7723-14-0, purity: 99.998%, was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0026] Graphene oxide, sheet diameter: 0.5-5 μm, item number: XF002-2, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0027] Glass fiber, model 508A, chopped strands, diameter 10-13 μm, length 3-4 mm, purchased from China Jushi Co., Ltd.
[0028] Comparative Example 1
[0029] A preparation process of a composite material for a frame structure comprises the following steps:
[0030] S1: 10 g of graphene oxide was weighed and dispersed in 1000 mL of water, ultrasonicated at 20°C, 400 W, 40 kHz for 2 h, then 10 g of HI aqueous solution was added for reduction, stirred for 5 h, filtered, and the filter cake was dried at 60°C for 12 h to obtain graphene;
[0031] S2 Weigh 5 g of γ-aminopropyltriethoxysilane and add it to 1 L of 80 wt% ethanol aqueous solution and stir for 2 h;
[0032] S3 weighs 60 g of dextran and adds it to the mixed solution in step S1, stirring for 2 hours to treat the dextran;
[0033] After the stirring in S4 is completed, the mixed solution is concentrated to dryness at 50°C and 0.09MPa, and then dried at 70°C for 12h to obtain the treated glucan;
[0034] S5: 200 g of caprolactam, 30 g of dextran treated in step S3, 5 g of graphene in step S1, 20 g of glass fiber and 2 g of styrene are mixed, and the mixed materials are melt-extruded and granulated. The process control conditions are: 170° C. in zone 1, 175° C. in zone 2, 177° C. in zone 3, 180° C. in zone 4, 180° C. in zone 5, 185° C. in zone 6, 190° C. in zone 7 and 190° C. in zone 8; the residence time is 2 min, the pressure is 12 MPa, and then the composite material for frame structure is obtained by drying at 60° C. for 12 h.
[0035] Example 1
[0036] A preparation process of a composite material for a frame structure comprises the following steps:
[0037] S1: Weigh 1 g of black phosphorus and disperse it in 200 mL of water. Ultrasonicate at 0°C, 400 W, 40 kHz for 5 h, centrifuge at 4000 rpm for 1 h, and take the supernatant.
[0038] S2: 10 g of graphene oxide was weighed and dispersed in 1000 mL of water, and then the supernatant in step S2 was added, and ultrasonicated at 20°C, 400 W, 40 kHz for 2 h, and then 10 g of HI aqueous solution was added for reduction, stirred for 5 h, filtered, and the filter cake was dried at 60°C for 12 h to obtain a black phosphorus-graphene composite material;
[0039] S3 weigh 5 g of γ-aminopropyltriethoxysilane and add it to 1 L of 80 wt% ethanol aqueous solution and stir for 2 h;
[0040] S4 weighs 60 g of dextran and adds it to the mixed solution in step S1, stirring for 2 hours to treat the dextran;
[0041] After the stirring in S5 is completed, the mixed solution is concentrated to dryness at 50°C and 0.09MPa, and then dried at 70°C for 12h to obtain the treated glucan;
[0042] S6: 200 g of caprolactam, 30 g of dextran treated in step S3, 5 g of black phosphorus-graphene composite material in step S2, 20 g of glass fiber and 2 g of styrene are mixed, and the mixed materials are melt-extruded and granulated. The process control conditions are: 170° C. in zone 1, 175° C. in zone 2, 177° C. in zone 3, 180° C. in zone 4, 180° C. in zone 5, 185° C. in zone 6, 190° C. in zone 7 and 190° C. in zone 8; the residence time is 2 min, the pressure is 12 MPa, and then the composite material for the frame structure is obtained by drying at 60° C. for 12 h.
[0043] Example 2
[0044] A preparation process of a composite material for a frame structure comprises the following steps:
[0045] S1: Weigh 1 g of black phosphorus and disperse it in 200 mL of water. Ultrasonicate at 0°C, 400 W, 40 kHz for 5 h, centrifuge at 4000 rpm for 1 h, and take the supernatant.
[0046] S2: 10 g of graphene oxide was weighed and dispersed in 1000 mL of water, ultrasonicated at 20°C, 400 W, 40 kHz for 2 h, then 10 g of HI aqueous solution was added for reduction, stirred for 5 h, filtered, and the filter cake was dried at 60°C for 12 h to obtain a black phosphorus-graphene composite material;
[0047] S3: 200 g of caprolactam, 5 g of the black phosphorus-graphene composite material in step S2, 20 g of glass fiber, and 2 g of styrene are mixed, and the mixed materials are melt-extruded and granulated. The process control conditions are: 170° C. in zone 1, 175° C. in zone 2, 177° C. in zone 3, 180° C. in zone 4, 180° C. in zone 5, 185° C. in zone 6, 190° C. in zone 7, and 190° C. in zone 8; the residence time is 2 min, the pressure is 12 MPa, and then the composite material for the frame structure is obtained by drying at 60° C. for 12 h.
[0048] Example 3
[0049] A preparation process of a composite material for a frame structure comprises the following steps:
[0050] S1: Weigh 1 g of black phosphorus and disperse it in 200 mL of water. Ultrasonicate at 0°C, 400 W, 40 kHz for 5 h, centrifuge at 4000 rpm for 1 h, and take the supernatant.
[0051] S2: 10 g of graphene oxide was weighed and dispersed in 1000 mL of water, and then the supernatant in step S2 was added, and ultrasonicated at 20°C, 400 W, 40 kHz for 2 h, and then 10 g of HI aqueous solution was added for reduction, stirred for 5 h, filtered, and the filter cake was dried at 60°C for 12 h to obtain a black phosphorus-graphene composite material;
[0052] S3: Weigh 2 g of 1-aminopyridine and 3 g of disuccinimidyl suberate, add them to 120 mL of N,N-dimethylformamide, stir for 12 h, then add 5 g of the black phosphorus-graphene composite material in step S2, continue stirring for 12 h, filter, wash the filter cake with 20 mL of N,N-dimethylformamide and 20 mL of anhydrous ethanol, respectively, and dry at 40 ° C for 2 h to obtain a black phosphorus-pyrene-based condensed ring-graphene composite material;
[0053] S4 Weigh 5 g of γ-aminopropyltriethoxysilane and add it to 1 L of 80 wt% ethanol aqueous solution and stir for 2 h;
[0054] S5: weighing 60 g of dextran and adding it to the mixed solution in step S1, stirring for 2 h to treat the dextran;
[0055] After the stirring in S6 is completed, the mixed solution is concentrated to dryness at 50°C and 0.09MPa, and then dried at 70°C for 12h to obtain the treated glucan;
[0056] S7: 200 g of caprolactam, 30 g of dextran treated in step S6, 5 g of black phosphorus-pyrene-based condensed ring-graphene composite material in step S3, 20 g of glass fiber, and 2 g of styrene are mixed. The mixed materials are melt-extruded and granulated. The process control conditions are: 170° C. in zone 1, 175° C. in zone 2, 177° C. in zone 3, 180° C. in zone 4, 180° C. in zone 5, 185° C. in zone 6, 190° C. in zone 7, and 190° C. in zone 8; the residence time is 2 min, the pressure is 12 MPa, and then the composite material for the frame structure is obtained by drying at 60° C. for 12 h.
[0057] Test Example 1
[0058] The impact strength test was conducted on the control example 1 and the example 1, and the test was conducted with reference to the method in GB / T 21189-2007 "Testing of pendulum impact tester for simple supported beam, cantilever beam and tensile impact test of plastics". The composite material was made into a 60mm×10mm×3mm strip sample and subjected to impact test using a simple supported beam impact tester. The impact-resistant supramolecular composite material obtained in each example was subjected to 5 parallel experiments and the arithmetic mean of the results was taken; the impact energy was calculated by the drop height of the impact head when the coating broke, and the unit was kJ / m 2 , in order to measure the impact toughness of the composite material. The test results are shown in Table 1.
[0059] Table 1 Impact strength test results
[0060] Experimental protocol <![CDATA[Impact strength / kJ / m 2 > Comparative Example 1 4.2 Example 1 5.1 Example 2 3.4 Example 3 5.5
[0061] According to Table 1, compared with Control Example 2, Example 3 can withstand greater impact strength. This is because the lubricating effect of black phosphorus leads to better dispersibility of the prepared black phosphorus-graphene composite material in the lightweight composite material, which improves the overall toughness of the material. The addition of dextran replaces part of the glass fiber, and the synergistic reinforcement effect of dextran itself and the glass fiber leads to the enhancement of the overall mechanical properties. On the other hand, the addition of dextran reduces the density of the composite material, resulting in a lighter material, which will provide a good foundation for the vehicle's endurance and energy saving. Treating it with a cross-linking agent not only increases the compatibility of dextran in the polymer, but also makes its dispersibility better. Example 3 Compared with Example 1, the black phosphorus-graphene composite material is further compounded, and a macromolecule with pyrene-based fused rings at both ends is generated through the amidation reaction of 1-aminopyrrolidone and disuccinimidyl suberate. The mechanical properties of the material are further improved, and the impact strength is also the largest. This may be because the large π bond of the molecule is combined with a large number of π electrons on the surface of graphene to form a π-π stacking effect, which successfully cross-links the black phosphorus-graphene molecules and produces a synergistic toughening effect.
[0062] Test Example 2
[0063] The bending strength test was carried out on the control example 1 and the embodiment 1, and the test was carried out with reference to the method in GB / T8812.2-2007 "Determination of bending properties of rigid foam plastics Part 2: Determination of bending strength and apparent bending elastic modulus". The sample length is 350mm, the thickness is 25mm, and the width is 100mm. The sample is placed symmetrically on the support, and the loading head is moved at a test speed of (20±1)mm / min. The pressure is applied perpendicular to the longitudinal axis of the sample, and the load is recorded to calculate the bending strength. The number of samples in each group is 5, and the arithmetic mean of the 5 samples is taken. The test results are shown in Table 2.
[0064] Table 2 Bending strength test results
[0065] Bending strength / MPa Comparative Example 1 40.3 Example 1 48.5 Example 2 37.1 Example 3 51.3
[0066] Compared with reference example 1, the mechanical strength of the composite material in embodiment 1 is higher, and the addition of dextran replaces part of the lightweight filler, reduces the density of the material, maintains a good bending modulus, can improve the bending strength of the composite material, and has a significant enhancement effect. The treatment of it by a cross-linking agent not only increases the compatibility of dextran in the polymer, but also makes its dispersibility better. Black phosphorus-graphene has a special lubricating effect due to the phosphorus atom, and the introduction will produce lubrication properties. At the same time, black phosphorus and graphene can also undergo POC covalent bond cross-linking. The two work together to enhance the toughness of the graphene composite material. When faced with increased load pressure, its enhanced toughness causes the material to be less easy to bend. In Example 3, black phosphorus-graphene is further combined, and a macromolecule with pyrene-fused rings at both ends is generated through the amidation reaction of 1-aminopyrrolidone and disuccinimidyl suberate, which together with the lubricating effect of black phosphorus improves the regularity, orientation and density of the graphene composite material. This may be due to the π-π stacking effect formed by the large π bond of the molecule and the large number of π electrons on the graphene surface, which successfully cross-links the various black phosphorus-graphene molecules, thereby improving the strength and toughness of the material, and then leading to the improvement of mechanical properties.
[0067] Test Example 3
[0068] The elongation at break was tested for Control Example 1 and Example 1, with reference to the standard of ISO527-2012 "Determination of tensile properties of plastics". The sample was stretched at a constant speed along the longitudinal main axis until the sample broke or its stress reached a predetermined value. The load and elongation of the sample during this process were measured, and its elongation at break was calculated. The elongation sample was 350 mm long, 25 mm thick, and 100 mm wide; each group of samples had 5 samples, and the result was the arithmetic average of the 5 samples.
[0069] Table 3 Elongation at break test results
[0070] Elongation at break / % Comparative Example 1 376.4 Example 1 261.3 Example 2 310.1 Example 3 206.9
[0071] As can be seen from Table 3, the elongation at break of the composite materials in Examples 1 and 3 is significantly reduced. This is because the addition of dextran in Example 1 replaces part of the lightweight filler, which reduces the density of the material, and can maintain a certain bending when subjected to stretching, so it is not easy to break. The treatment of it with a cross-linking agent can make the dextran more dispersed in the polymer, so it is not easy to agglomerate and cause the material to break. Black phosphorus-graphene has a special lubricating effect due to the phosphorus atom, and the introduction will produce lubrication properties. At the same time, black phosphorus and graphene can also undergo POC covalent bond cross-linking. The two work together to enhance the toughness of the graphene composite material, and its enhanced toughness causes the material to be difficult to break when facing the load increase pressure. In Example 3, a macromolecule with pyrene-containing fused rings at both ends was generated by the amidation reaction of 1-aminopyrrolidone and disuccinimidyl suberate, which, together with the lubricating effect of black phosphorus, improved the regularity, orientation and density of the graphene composite material. This may be because the large π bond of the molecule combined with the large number of π electrons on the graphene surface to form a π-π stacking effect that successfully cross-linked the black phosphorus-graphene molecules, thereby improving the strength and toughness of the material, and thus its elongation at break was the lowest.
Claims
1. A composite material for a frame structure, characterized in that: The main components include: caprolactam, treated dextran, black phosphorus-graphene composite material, inorganic filler and cross-linking agent.
2. The composite material for frame structure according to claim 1, characterized in that: The invention mainly comprises the following raw materials in parts by weight: 100-200 parts of caprolactam, 30-40 parts of treated dextran, 5-10 parts of black phosphorus-graphene composite material, 10-20 parts of inorganic filler and 1-2 parts of cross-linking agent.
3. The composite material for frame structure according to claim 1 or 2, characterized in that: The inorganic filler is one of calcium carbonate, talcum powder or glass fiber.
4. The composite material for frame structure according to claim 1 or 2, characterized in that: The cross-linking agent is one of styrene, methyl methyl benzoate or ethyl methyl benzoate.
5. The process for preparing the composite material for frame structure according to any one of claims 1 to 4, characterized in that: The steps include: S1: Weigh 1-5 parts by weight of γ-aminopropyltriethoxysilane and add it to 100-200 parts by weight of 70-80 wt% ethanol aqueous solution and stir for 1-2 hours; S2 weighs 30 to 60 parts by weight of dextran and adds it to the mixed solution in step S1, and stirs for 2 to 4 hours to treat the dextran; After the stirring in S3 is completed, the mixed solution is concentrated to dryness at 40-50°C and 0.09MPa0.07-0.09MPa, and then dried at 60-70°C for 10-12h to obtain the treated glucan; S4: weigh 1-2 parts by weight of black phosphorus and disperse it in 100-200 parts by weight of water, ultrasonicate it at 0-5°C, 400-450W, 40-45kHz for 5-6h, centrifuge it at 4000-4500rpm for 1-2h, and take the supernatant; S5: weighing 10-20 parts by weight of graphene oxide and dispersing it in 1000-1500 parts by weight of water, adding the supernatant in step S4, ultrasonicating at 10-20° C., 400-450 W, 40-45 kHz for 1-2 hours, stirring for 20-24 hours, adding HI aqueous solution for reduction, stirring for 5-6 hours, filtering, and drying the filter cake at 50-60° C. for 10-12 hours to obtain a black phosphorus-graphene composite material; S6: 100-200 parts by weight of caprolactam, 30-40 parts by weight of dextran treated in step S3, 5-10 parts by weight of black phosphorus-graphene composite material, 10-20 parts by weight of inorganic filler, and 1-2 parts by weight of coupling agent are mixed; the mixed material is melt-extruded, granulated, and dried to obtain a composite material for a frame structure.
6. The process for preparing the composite material for frame structure according to claim 5, characterized in that: The HI aqueous solution described in step S5 is 10 to 20 parts by weight.
7. The process for preparing the composite material for frame structure according to claim 5, characterized in that: The process control conditions described in step S6 are: zone one 170-175°C, zone two 170-175°C, zone three 175-180°C, zone four 175-180°C, zone five 180-185°C, zone six 180-185°C, zone seven 185-190°C, zone eight 185-190°C.
8. The process for preparing the composite material for frame structure according to claim 5, characterized in that: The extrusion residence time described in step S6 is 2 to 4 minutes.
9. The process for preparing the composite material for frame structure according to claim 5, characterized in that: The extrusion pressure in step S6 is 12 to 18 MPa. The process for preparing the composite material for frame structure according to claim 5, characterized in that: The drying temperature in step S6 is 60-80° C. and the drying time is 10-12 hours.
Citation Information
Patent Citations
Thermoplastic light-weight composite material and preparation method thereof
CN107903627A
Environmentally-friendly engineering plastic for lightweight automobiles
CN108727790A